Institutional implications of the Defence Force's submission to the Truth and Reconciliation Commission - Sankar, Anesh Munessar (My University, 2014)
During the twentieth century there have been several instances of military institutions appearing before Truth and Reconciliation Commissions (TRC's) to account for past activities. Quite often the military resisted the disclosure of information and the acceptance of responsibility for their actions. The purpose of this study is to assess the disclosure and accountability displayed by the former South African Defence Force (SADF) before the TRC, and the possible future institutional implications. The main findings are that the former SADF sought to avoid disclosing past activities and accepting accountability for them. The new leadership of the South African National Defence Force (SANDF) did not engage in the TRC process in order to maintain political stability among their soldiers. Implications for the future are that there could be a continuing effect of these unresolved issues, which could become a threat to the military institution as well as to the broader society.